2013
DOI: 10.1002/chem.201300451
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐faceted Reactivity of Alkyltellurophenols Towards Peroxyl Radicals: Catalytic Antioxidant Versus Thiol‐Depletion Effect

Abstract: Hydroxyaryl alkyl tellurides are effective antioxidants both in organic solution and aqueous biphasic systems. They react by an unconventional mechanism with ROO(·) radicals with rate constants as high as 10(7)  M(-1)  s(-1) at 303 K, outperforming common phenols. The reactions proceed by oxygen atom transfer to tellurium followed by hydrogen atom transfer to the resulting RO(·) radical from the phenolic OH. The reaction rates do not reflect the electronic properties of the ring substituents and, because the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

8
2

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 82 publications
5
84
0
Order By: Relevance
“…We have found a conceptually different way to improve the radical‐trapping activity of phenols. The seminal observation we made some time ago was that alkyltellurophenols could quench lipid peroxyl radicals with k inh >10 7 m −1 s −1 . Because the rate constant for the reaction of phenol itself with peroxyl radicals is only in the order of 10 3 m −1 s −1 , we proposed an unconventional mechanism for the reaction, that involved oxygen‐atom transfer from the peroxyl radical to tellurium, followed by hydrogen‐atom transfer from phenol to the resulting alkoxyl radical (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…We have found a conceptually different way to improve the radical‐trapping activity of phenols. The seminal observation we made some time ago was that alkyltellurophenols could quench lipid peroxyl radicals with k inh >10 7 m −1 s −1 . Because the rate constant for the reaction of phenol itself with peroxyl radicals is only in the order of 10 3 m −1 s −1 , we proposed an unconventional mechanism for the reaction, that involved oxygen‐atom transfer from the peroxyl radical to tellurium, followed by hydrogen‐atom transfer from phenol to the resulting alkoxyl radical (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…9 Several studies support the introduction of 3 rd period and higher chalcogen atoms as another effective means of enhancing the antioxidant capacity of phenolic compounds. 10,11 Selenium-substitution was found to enhance the chain breaking activity via a decrease in the BDE values of the phenolic groups. 12,13 Similarly, the introduction of an octyltelluro group into the β-or δ-tocopherol system resulted in more efficient quenching of peroxyl radicals via an unusual oxygen transfer process to the chalcogen in the presence of N-acetylcysteine.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 In this work, we found that alkyltelluro groups have a remarkable effect. For example, introducing an octyltelluro group next to the OH in phenol caused a ca.…”
mentioning
confidence: 60%